PEMILIHAN LOKASI TERBAIK PENGEMBANGAN PROPERTI APARTEMEN DI PERKOTAAN CIBINONG RAYA KABUPATEN BOGOR - Muhammad Saifuddin Amanullah; Ragil Haryanto (Jurnal Pengembangan Kota, 2017)
As a part of Greater DKI Jakarta or known as Jabodetabek, Cibinong Raya offers alternatives for residence location. The statistic of population in Cibinong noted that its population has grown by 16.37% (BPS Bogor Regency, 2016) that has implication on the increase of residential dwelling demand. However, the amount of non-built area in the city is limited. So, land use optimazition strategy is significant to reach the optimum land-use value. The result of this study is expected to give different perpective of property development applied by the property developers in Indonesia. Hence, this research applied variables derived from the literature reviews and asked the property experts to analyse the variables. Using Analytical Hierarchy Process (AHP), it was revealed that there were four suitable alternative location named as Location A, Location B, Location C and Location D. Based on the experts perception through AHP method, the study showed that the highest optimum value was Location D (0.336) and followed by Location A (0.309), Location C (0.218) and Location B (0.139).